TURBULENT STRESS DISTRIBUTION IN THE TURBULENT BOUNDARY LAYER ON A PERMEABLE POROUS PLATE - Vlassov, D.; Vargas, J. V. C.; Ordonez, J. C.; Martins, L. S. (Revista de Engenharia Térmica, 2006)
In this paper the results of experimental tests on turbulent boundary layer on a plate with air blowing through permeable porous wall are presented. Tests were performed in an aerodynamic tunnel varying the blowing rate within the range of 0 to 2.5% of the air flow velocity in the tunnel, using thermoanemometers of constant temperature. It has been determined that the blowing increases the boundary layer thickness and strongly transforms the boundary layer inner part and turbulent nucleus, while the outer part remains not deformed. An increase in blowing causes an abrupt viscous stress decrease, also decreasing skin friction. Thick boundary layers (up to 120 mm) allowed a profound analysis of Reynolds’ turbulent stresses. It has been found a general distribution of turbulent stress in the turbulent layer which is independent of blowing velocity. It has been established for the turbulent characteristics that the determining coordinate is the relative horizontal velocity, not the distance from the wall. With a turbulent stress database obtained from turbulent stresses direct measurements, it has been proposed a flow model for boundary layer on a permeable porous plate. It has also been demonstrated that in high blowing conditions the horizontal velocity profile in the boundary layer becomes equal to the velocity profile in a plane jet.